Diagnostic accuracy of oral swab for detection of pulmonary tuberculosis: a systematic review and meta-analysis - Zhang, Fuzhen; Wang, Yilin; Zhang, Xuxia; Liu, Kewei; Shang, Yuanyuan; Wang, Wei; Liu, Yuanyuan; Li, Liang; Pang, Yu (Frontiers in Medicine, 2024)
Objectives Tuberculosis (TB) remains a significant concern in terms of public health, necessitating the timely and accurate diagnosis to impede its advancement. The utilization of oral swab analysis (OSA) presents a promising approach for diagnosing pulmonary TB by identifying Mycobacterium tuberculosis (MTB) within oral epithelial cells. Due to disparities in the diagnostic performance of OSA reported in the original studies, we conducted a meticulous meta-analysis to comprehensively assess the diagnostic efficacy of OSA in pulmonary TB. Methods We conducted a comprehensive investigation across multiple databases, namely PubMed, Cochrane Library, Embase, Web of Science, ClinicalTrials.gov, Chinese BioMedical Literature Database (CBM), China National Knowledge Infrastructure Database (CNKI), and Wanfang China Science and Technology Journal Database to identify relevant studies. Out search query utilized the following keywords: oral swab, buccal swab, tongue swab, tuberculosis, and TB. Subsequently, we employed STATA 16.0 to compute the combined sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, and diagnostic odds ratio for both the overall and subgroup analyses. Results Our findings indicated that OSA has a combined sensitivity of 0.67 and specificity of 0.95 in individuals with pulmonary TB. Subgroup analysis further revealed that among adult individuals with pulmonary TB, the sensitivity and specificity of OSA were 0.73 and 0.93, respectively. In HIV-negative individuals with pulmonary TB, the sensitivity and specificity were 0.68 and 0.98, respectively. The performance of OSA in detecting pulmonary TB correlated with the bacteria load in sputum. Additionally, the sensitivity for diagnosing pulmonary TB using tongue specimens was higher (0.75, 95% CI: 0.65–0.83) compared to cheek specimens (0.52, 95% CI: 0.34–0.70), while both types of specimens demonstrated high specificity. Conclusions To conclude, oral swabs serve as a promising alternative for diagnosing pulmonary TB, especially in adult patients. In addition, tongue swabs yield better sensitivity than cheek swabs to identify pulmonary TB patients. Systematic review registration identifier: CRD42023421357.